The incidence of type 2 diabetes mellitus and the traditional risk factors of carbohydrate metabolic disorders in patients with rheumatoid arthritis - L. V. Kondratyeva; T. V. Popkova (Современная ревматология)
Objective: to clarify the primary incidence of type 2 diabetes mellitus (DM) in patients with rheumatoid arthritis (RA) and to compare the prevalence of traditional risk factors (RFs) in groups of patients with and without carbohydrate metabolic disorders.Patients and methods. A retrospective analysis was carried out in 158 patients with RA (diagnosed at the age of 45 years and older; the disease duration was more than 12 months). The exclusion criteria were concomitant type 1 DM and type 2 DM that was diagnosed before or at the onset of RA. The patients' median age was 62 [57; 68] years. Most RA patients had moderate (41.8%) and high (39.9%) DAS28. New cases of type 2 DM and the presence of hyperglycemia were recorded at the time of the examination. The traditional RFs of type 2 DM were assessed using the Finnish Diabetes Risk Score (FINDRISC).Results and discussion. The incidence rates of type 2 DM was 9.3 per 1000 patient-years. The patients with developed type 2 DM versus those without DM had a larger number of RFs according to the the FINDRISC questionnaire (6 [5; 7] and 5 [4; 5]; p<0.01), had more frequently experienced myocardial infarction and undergone surgery for myocardial revascularization (27.3 and 2.7%; p<0.01), taken beta-adrenoblockers (72.7 and 33.3%; p<0.05) and calcium channel blockers (36.4 and 12.2%; p<0.05). Fasting hyperglycemia was detected in 10.1% of RA patients. The patients with hyperglycemia versus those with normal venous blood glucose levels more often had obesity (50.0 and 29.8%) and a history of hyperglycemic episodes (43.8 and 19.1%) and less frequently used glucocorticoids (18.8 and 47.3%; p<0.05 for all cases). Conclusion. The high incidence of type 2 DM in RA was associated with the presence of a set of traditional RFs and previous cardiovascular disease, while fasting hyperglycemia was with individual RFs for carbohydrate metabolic disorders.